Epigenetic programming defines haematopoietic stem cell fate restriction - Meng, Y; de Teixeira Carrelha, J; Drissen, R; Ren, X; Zhang, B; Gambardella, A; Valletta, S; Thongjuea, S; Jacobsen, SE; Nerlov, C (Springer Nature, 2023)
Haematopoietic stem cells (HSCs) are multipotent, but individual HSCs can show restricted lineage output in vivo. Currently, the molecular mechanisms and physiological role of HSC fate restriction remain unknown. Here we show that lymphoid fate is epigenetically but not transcriptionally primed in HSCs. In multi-lineage HSCs that produce lymphocytes, lymphoid-specific upstream regulatory elements (LymUREs) but not promoters are preferentially accessible compared with platelet-biased HSCs that do not produce lymphoid cell types, providing transcriptionally silent lymphoid lineage priming. Runx3 is preferentially expressed in multi-lineage HSCs, and reinstating Runx3 expression increases LymURE accessibility and lymphoid-primed multipotent progenitor 4 (MPP4) output in old, platelet-biased HSCs. In contrast, platelet-biased HSCs show elevated levels of epigenetic platelet-lineage priming and give rise to MPP2 progenitors with molecular platelet bias. These MPP2 progenitors generate platelets with faster kinetics and through a more direct cellular pathway compared with MPP2s derived from multi-lineage HSCs. Epigenetic programming therefore predicts both fate restriction and differentiation kinetics in HSCs.